Tonir in the Armenian oral culture - Arakelyan , Siranuysh (History and Culture, 2025)
The tonir (hearth) in Armenian culture is deeply linked to the worship of fire and ancestors, leaving its mark on folklore, beliefs, festivals, and customs. It was not merely a household object but also held a multifunctional, sacred role, serving the religious needs of the family and community. In some villages, certain tonirs even acquired the significance of sacred places. The functions of the tonir ranged from baking bread to performing wedding and baptism rituals, healing to protection from evil, divination to transformation, wishes and vows, and as a pilgrimage site. The Armenians regarded it as the sanctified place of the home, based on the belief that the spirits of family ancestors lived within the tonir’s  flame or at its edge. In villages without churches, the tonir even “substituted” for a Christian temple, where baptisms and weddings took place.In Armenian oral culture, legends, tales, and riddles have developed around the tonir, and it has been mentioned in traditional wedding songs as well. In almost every region of the Armenian Highlands, people swore “by the sacred tonir”—a trusted oath that encouraged others to believe in the truthfulness of the swearer’s words.
Keywords: tonir; sacred space; oral tradition; ritual; fire; water; ashes; beliefs